The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fmicb.2022.868890
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas and Human Health Disorders: Clinical Approaches

Abstract: The genus Aeromonas comprises more than 30 Gram-negative bacterial species and naturally inhabitants from aquatic environments. These microorganisms, commonly regarded as pathogens of fish and several other animals, have been gaining prominence on medical trial due to its ability to colonize and infect human beings. Besides water, Aeromonas are widely spreaded on most varied sources like soil, vegetables, and food; Although its opportunistic nature, they are able to cause infections on immunocompromised or imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 171 publications
0
23
0
Order By: Relevance
“…was first isolated from pneumonia, wound infections, septicemia, and abortion in horses, cattle, and pigs in 1987 [ 24 ]. It is known as a threat to aquaculture systems and human health, causing a high death rate [ 3 , 25 ]. As an important member of Aeromonas , A. veronii is pathogenic to both aquatic and terrestrial animals [ 7 , 8 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…was first isolated from pneumonia, wound infections, septicemia, and abortion in horses, cattle, and pigs in 1987 [ 24 ]. It is known as a threat to aquaculture systems and human health, causing a high death rate [ 3 , 25 ]. As an important member of Aeromonas , A. veronii is pathogenic to both aquatic and terrestrial animals [ 7 , 8 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenicity results revealed that the strain is pathogenic to both sheep and mice. Thus, A. veronii is not only an important threat to the sheep industry, but also poses a potential threat to human health, as the infection may spread to humans via the consumption of undercooked meat contaminated with A. veronii [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no report mentions Aeromonas sobria as a new candidate for heavy metals removal. Aeromonas species generally associated with human infections include A. caviae, A. schubertii, A. hydrophila, A. veronii (biovars veronii and sobria), and A. jandaei 30 ; however, biochemically distinct A. veronii biovar sobria have been predominantly found in clinical isolates 31 . Our results show that A. sobria can tolerate high concentrations of different heavy metals.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been no reports of outbreaks of A. hydrophila in Japan in recent years, it is still challenge as a causative agent of diarrheal infections in other parts of the world. 38) Well water may be used as drinking water in times of disaster. Therefore, it is necessary to use gastrointestinal infection-causing bacteria as indicator bacteria for the safety and quality of well water.…”
Section: Physicochemical Characteristics Of Well Water and Bacterial ...mentioning
confidence: 99%